The influence of knowledge, effort and ethical orientation on audit judgement performance / Razana Juhaida Johari ... [et al] - Johari, Razana Juhaida; Mohd Sanusi, Zuraidah; Abdul Bakar, Rashidah; Omar, Normah (PENERBIT PRESS Universiti Teknologi MARA, 2022)
The current study examines the relationship between ethical orientation, knowledge and effort on audit judgment performance amongst final year accounting students who are the potential future auditors of Malaysia. The research instrument was developed and self-administered to 220 Accounting students enrolled in Diploma in Accountancy and Bachelor of Accountancy in Universiti Teknologi MARA (UiTM). The study measures the ethical orientation in two dimensions - idealism and relativism, The multiple regression results show that there is a significant relationship between the respondent’s knowledge and effort on audit Judgment performance. However, contrary to the expectation, effort indicates significantly a negative relationship to audit judgment performance. In overall, the study reveals that the differences in one’s ethical orientation are insignificant to predict their judgment in auditing context. It also suggests that different group of students show different effect of knowledge and effort on the audit Judgment performance.